Cultural Transgressions in Omar S. Castañeda’s Remembering to Say ‘Mouth’ or ‘Face’ - Alicia Ivonne Estrada (Studies in 20th & 21st Century Literature, 2013)
This study examines the ways Omar S. Castañeda’s Remembering to Say ‘Mouth’ or ‘Face’ (1993) deconstructs national and hyphenated identities. It argues that rooting these short stories within the Popol Wuj’s narrative structure allows for the construction of different historical references and cultural genealogies, which are not solely based on national identities or histories. This is evident in the second section entitled “Crossing the Border,” which blends myths from the Popol Wuj with the characters, contemporary historical contexts in the United States and Guatemala. At the same time, the stories illustrate the protagonists’ multiple displacements, but also their links to the histories and cultures of indigenous, specifically Maya, peoples in the Americas. Consequently these displacements and connections result in the search as well as the creation of alternative narratives of belonging that are attuned to the characters’ multiple embodied subjectivities and positionalities. By grounding the protagonists’ cultural genealogies within Maya mythical and historical frameworks that emphasize difference, Castañeda’s text highlights the multiple identities of Guatemalans in that country and the diaspora.
Keywords: Omar S. Casteñeda; cultural transgressions; national identity; hyphenated identity; Popol Wuj; contemporary historical context; US; Guatemala; indigenous; Maya; diaspora